Cross-cultural adjustment experiences of academic expatriates in some South African universities: The case of KwaZulu-Natal - Ngonyama-Ndou, T. (South African Journal of Higher Education, 2020)
This article discusses the cross-cultural adjustment experiences of selected academic expatriates from selected South African universities based in the KwaZulu-Natal Province. Quantitative data was collected from 142 out of 277 academic expatriates. Statistical procedures were used to analyse, interpret and make meaning of the raw data. The findings revealed that academic expatriates experience general and interaction adjustment challenges associated with the use of local languages and the understanding of local culture. However, female academic expatriates were found to be better adjusted in interaction and general adjustment as compared to their male counterparts. Furthermore, work adjustment challenges triggered by the poor coordination of work permit application were also discovered. The study stressed revision of human resources practices, immigration policies as well as cross-cultural adjustment support for academic expatriates into South African host academic institutions.